Quizizz sebagai Media Alternatif dalam Mendukung Peningkatan Keterampilan Istima’ - Nuraisyah, Andini; Akhyara, Hiqwah Safira; Umbar, Kisno (Kalimatuna: Journal of Arabic Research, 2023)
Since the emergence of the covid-19 outbreak, the learning system which was originally face-to-face in schools, now has to be done remotely (online).  This applies to all levels of education, both schools and universities.  Therefore, now there are many application designers to carry out and facilitate distance learning (online), one of which is by using the Quizizz application.  quizizz is considered as an innovative medium because it contains interesting features so that distance learning does not feel boring. This study uses a descriptive qualitative approach in which the researcher describes the definitions and mechanisms for using the Quizizz application as a medium to support distance learning. The things that will be discussed in this study include: 1.) what features can I use in istima learning? 2.) what are the steps for using quizizz in istima learning? 3.) what are the advantages of the Quizizz application in istima learning? 4.) and what are the problems encountered in learning istima' using Quizizz?